CFD Prediction of the Most Appropriate Values of Prandtl Kolmogorov Constant in the Turbulent Boundary Layer - Abbas, Nawar (Latakia University Journal -Engineering Sciences Series, 2019)
This study aims to determine the scope of application and accuracy of the Prandtl Kolmogorov formula, through which the turbulence length scale L can be calculated, by selecting the most appropriate value of the experimental constant C used in this formula using CFD (Computational Fluid Dynamic) technique and comparing the results with the experimental data. One of the most important applications of this formula is in hybrid turbulence models in CFD in which the computational domain must be divided into two regions. In the first region near to the wall, the URANS method (Unsteady Reynolds Averaged Navier Stokes Equations) is applied and in the second region far from the wall, the LES method (Large Eddy Simulation) is applied. The open-source program (OpenFOAM), URANS method and k-ω SST turbulence model have been used to perform the numerical calculations. The numerical results show a good agreement with the experimental data, which confirms the accuracy of the CFD solution in fluid dynamic applications and the accuracy of the Prandtl Kolmogorov Formula in the calculation of turbulent length scale. يهدف هذا البحث إلى اختبار دقة ومجال تطبيق علاقة براندتل كولموغوروف والتي من خلالها يتم حساب الطول المميز للاضطراب (الدوامة) ، وذلك من خلال اختيار القيمة الأنسب للثابت التجريبي المستخدم في هذه العلاقة باستخدام تقنية الـ CFD ومقارنة النتيجة مع النتائج التجريبية. من أهم تطبيقات هذه العلاقة هي استخدامها لتقسيم المجال الحسابي في نماذج الاضطراب الهجينة (Hybrid turbulence models) في تقنية الـ CFD حيث يتم أثناء استخدام هذه النماذج تقسيم المجال الحسابي إلى قسمين، القسم الأول وهو بالقرب من الجدار، حيث تتشكل وتتطور الطبقة الحدية، يتم فيه استخدام طريقة الـ URANS (Unsteady Reynolds Averaged Navier Stokes Equations)، وفي القسم الثاني، بعيدا عن الجدار، يتم استخدام طريقة LES (Large Eddy Simulation). تم استخدام برنامج الـ OpenFOAM لإجراء حسابات الـ CFD، وتم استخدام طريقة الـ URANS ونموذج الاضطراب من أجل حساب الجريان ومن ثم حساب قيمة . النتائج التي تم الحصول عليها من الـ CFD تمت مقارنتها مع النتائج التجريبية. المقارنة تبين بأن هناك تطابق كبير بين الحسابات الرقمية والنتائج التجريبية، و هذا يؤكد لنا مدى دقة وجودة تقنية الـ CFD في حساب الجريانات، كما ويؤكد في نفس الوقت قدرة علاقة براندتل كولموغوروف على حساب الطول المميز للاضطراب.